Antioxidant Composition of Guava (Psidium guajava L.) Beverage Blended with Black-Carrot Juice - V S Khandare (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
An investigation was undertaken to study guava beverage blended with black-carrot juice, during 2011-2012. Enzyme-assisted processing of guava significantly improved the juice yield, total soluble solids, titratable acidity pH, ascorbic acid and sugars by using pectinase enzyme. The blending of guava beverage with black carrot juice significantly improved the functional properties of the guava RTS. Anthocyanin and ascorbic contents of blended guava RTS with black-carrot juice decreased with advancement of storage condition and period.